Letters, a secret and power in Durante la Reconquista by Alberto Blest Gana (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
Durante la Reconquista by Alberto Blest Gana can be read as a novel in which a secret and power are intertwined in a profoundly significant manner. This interrelationship is constituted in the narrative support, in which the development of historical events, amorous intrigues and social customs are all interwoven. In the unfolding of the novel we can find the inscription of the political and ethical concerns of the author.
Keywords: Chilean realist novel; epistolary genre; reading and readers; literatura and evil